An influencer pathway framework for sustainable tourism in SIDS ecotourism hotspots: A case of Aripo ecosystems, Trinidad - Wuddivira, Mark N.; De Caires, Sunshine A.; Joseph, Jeanelle; Atwell, Melissa A.; Lewis-Cameron, Acolla (Frontiers in Sustainable Tourism, 2023)
Ecotourism hotspots in small island developing states (SIDS) are affected by unsustainable practices characterized by a lack of coordination, management inadequacies, and poor enforcement of policies and regulations. Consequently, depletion of natural resources and reduction in ecosystem value occur, with the undermining of the contribution of tourism to SIDS economies. An ecotourism system that ensures sustainable ecological integrity, economic viability, and social awareness is therefore critical in SIDS. We developed an influencer ecotourism pathway framework (IPF) using the Aripo ecosystem as a case study of an ecotourism hotspot by focusing on influencers within a SIDS system to improve collaboration towards the common goal of ecosystem sustainability. The framework was created to reflect the ecosystem attributes and services found in Aripo, the influencers that both negatively and positively impact the environment, possible solutions specific to addressing these negative impacts, and the ecotourism goals of the area. The framework was used to characterize the natural capital of Aripo in relation to the three (3) main ecosystems: forest, savanna, and man-made Aripo village. The influencer ecotourism framework provides a practical model to be applied for sustainable ecotourism management efforts in tropical small island regions as it identifies ecotourism attributes and ecosystem services, linking them to the potential impacts of influencers on the environment. It also provides useful insights to various influencers about their role in sustainable ecotourism that conserves the natural capital of the destination community while improving socioeconomic conditions.